FEMINICÍDIO: estudo sobre as decisões proferidas pelo Tribunal de Justiça do Estado do Maranhão no âmbito da Lei n. 13.104/2015. - FAÇANHA, Josanne Cristina Ribeiro Ferreira (2021)
The thesis entitled “Feminicide: a study on the decisions handed down by the Maranhão State Court of Justice under Law no. 13.104 / 2015” aimed at analyzing the decisions handed down by the Maranhão State Court between the years 2015 to 2019, using the Maria da Penha Law and the Feminicide Law as parameters. This is a qualitative research, exploratory in nature, anchored in documentary and bibliographic contributions, focusing on the decisions made by the Maranhão State Court of Justice, specifically with regard to the cases of femicides that occurred between the years 2015 to 2019. Initially, the configuration of domestic violence is presented as gender violence and human rights violations, thus framing women's rights based on the Universal Declaration of Human and Citizen Rights, formulated by the United Nations in 1948, focusing on issues related to international treaties and agreements on women's rights arising after the Universal Declaration of Rights, and ratified by Brazil, incorporated by the constitutional text. Then, the origin of the term feminicide was discussed, its criminalization and confrontation by the Judiciary, in the light of the Maria da Penha Law and, later analysis of the judgments related to the crimes of feminicide in Maranhão, in the chosen time frame. It was concluded that, despite the positivity of the legal advances with the Maria da Penha and Feminicide laws, difficulties persist for their effective implementation with the target audience for which they are intended to protect. There were ambiguous interpretations, distortions in the decisions rendered in relation to what the Maria da Penha law says, along with the mismatch between the number of cases brought to the attention and appreciation of the Maranhão State Court (32 cases) in the years of 2015 to 2019 and statistical data on femicide in the State of Maranhão, which, in 2019, occupied the 5th position in the ranking of the Northeast Region. Revealing results of difficulties and challenges in making women's rights in Brazil effective, especially black, old, poor, which contributes to the increase in the number of gender-based violence and feminicides, naturalization of the patriarchy / racism / capitalism triad, invisibility of their victims, multiple attacks on human rights and impacts on all spheres of social life.